Gender differences in estimates of reversal motivational intelligences for self and others: A replication in Brazil - Neto, Félix (Anales de Psicología / Annals of Psychology, 2018)
This research approached gender differences in self- and other-estimated overall, reversal motivational intelligences and beliefs about intelligence in Brazil. The sample comprised 174 (96 women and 78 men) students. Participants answered a survey where they estimated their parents’, partners’ and own overall and the eight reversal motivational intelligences. They also evaluated six factors about intelligence. Men assessed their overall intelligence higher than women. By contrast, women provided greater self-estimates of alloic mastery and alloic sympathy intelligences than men. Women and men did not differ in estimates of partner and of parental reversal motivational intelligences. Respondents rated their father as more intelligent than their mothers. In general, respondents evaluated themselves as more intelligent than their parents. Fathers have been rated as more intelligent than mothers on overall intelligence. Telic and conformist intelligences were significant predictors of overall intelligence. Factor analysis of the eight reversal motivational intelligences evidenced a unidimensional structure. Most of respondents did not believe in gender differences in intelligence. The results are discussed taking into account the extant literature in the field.